2019
DOI: 10.1177/0971721819873180
|View full text |Cite
|
Sign up to set email alerts
|

Institutional Factors for Academic Entrepreneurship in Publicly owned Universities in Japan: Transition from a Conservative Anti-industry University Collaboration Culture to a Leading Entrepreneurial University

Abstract: The establishment of university spin-offs differs across schools as a result of the interactions among different intuitional settings. This study examines the role of institutional factors in the context of state-controlled universities, which are the majority in East Asia, but have not been the focus of the existing literature. The University of Tokyo experienced a significant shift from an anti-industry university collaboration culture to a leading entrepreneurial university in the mid-2000s. This study prop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 35 publications
0
6
0
1
Order By: Relevance
“…Almeida et al (2020), além das mudanças tecnológicas, surgem, paralelamente, concepções inovadoras que envolvem os alunos, professores e as metodologias. Para Barnard, et al, (2019) (Clark,1998(Clark, , 2006Etzkowitz, 2013;Urbano & Guerreiro, 2013;Riviezzo et al, 2018;Krabel, 2018;Yoshioka-Kobayashi, 2019) à performance empreendedora, que implica mensurar autonomia, inovatividade, assumir riscos, proatividade e agressividade competitiva (Lumpkin & Dess, 1996).…”
Section: Base Financeira Multiunclassified
“…Almeida et al (2020), além das mudanças tecnológicas, surgem, paralelamente, concepções inovadoras que envolvem os alunos, professores e as metodologias. Para Barnard, et al, (2019) (Clark,1998(Clark, , 2006Etzkowitz, 2013;Urbano & Guerreiro, 2013;Riviezzo et al, 2018;Krabel, 2018;Yoshioka-Kobayashi, 2019) à performance empreendedora, que implica mensurar autonomia, inovatividade, assumir riscos, proatividade e agressividade competitiva (Lumpkin & Dess, 1996).…”
Section: Base Financeira Multiunclassified
“…Among the institutional factors, previous works have highlighted the important role of technology transfer offices (TTO) (Markman et al, 2005;Ambos et al, 2008;Greenbaum and Scott, 2010;Calder on-Mart ınez and Garc ıa-Quevedo, 2013;Wu et al, 2015), the incentives existing in each university for researchers to opt to commercialize their research results (Macho-Stadler et al, 1996, 2007Jensen and Thursby, 2001;Lach and Schankerman, 2004;Link and Siegel, 2005;Baldini et al, 2007), and the existing regulations in each university regarding the transfer of results (Owen-Smith and Powell, 2001;Yoshioka-Kobayashi, 2019). Some authors have demonstrated the influence of the existence of financial support from the industry in pre-patent research (Friedman and Silberman, 2003), while others analyze the effect of the scientific field on the transfer of research results (Azoulay et al, 2007).…”
Section: Theoretical Background and Hypothesesmentioning
confidence: 99%
“…Intermediaries were underdeveloped and conditions for product tests were not good enough (Poppen & Decker, 2018). A good cultural climate for university entrepreneurship was in shortage (Yoshioka-Kobayashi, 2019). Organisations and structures did not collaborate well with each other (Wirsich et al, 2016).…”
Section: U-e Innovation Chain Researchesmentioning
confidence: 99%